A note on the design of cancer screening trials. (June 2015) - Duffy, Stephen W; Smith, Robert A
Objectives: To investigate the consequences of different cancer screening trial designs and follow-up options for accuracy of the estimate of the effect of screening on disease-specific mortality. Methods: We consider a randomized trial of breast cancer screening with a screening phase in which the intervention group is offered screening and the control group is not, and optional further follow-up after this screening phase. Postulating a lead time effect similar to that observed in breast cancer screening trials, we calculate the observed relative risk of disease-specific mortality and compare this with the true relative risk, for four design options: (1) no follow-up beyond the screening phase, ie. the screening phase and the observation period are identical; (2) follow-up continuing beyond the screening phase, all cancer-specific deaths counted, including those diagnosed after the screening phase; (3) follow-up continuing beyond the screening phase, but with only deaths from cancers diagnosed during the screening phase included; and (4) follow-up continuing beyond the screening phase, a single screen of the control group conducted at the end of the screening phase, and only deaths from cancers diagnosed during the screening phase in both arms up to completion of the single control screen included. Results: All designs in which follow-up for mortality continues beyond the screening phase incurred a bias against screening. The design in which the control group undergoes a single screen at the end of the screening phase was least biased in the example used. Conclusions: The expedient of a single screen of the control group at the end of the screening phase has acceptable accuracy, but is still slightly conservatively biased.